The influence of particle size on the nature and transport of sediments and associated pollutants in urban stormwater drainage - Morgan, David Thomas (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2014)
The sediment and pollutant load transported by pipe and gully stormwater drainage systems was investigated through field sampling of a number of urban catchments. Stormwater runoff from a residential catchment was monitored over an 18-month period, during which time 19 rain events were analysed for a range of pollutant parameters including suspended solids concentration (SSC), volatile suspended solids, particle size distribution (PSD), heavy metals and total phosphorus.
Keywords: Civil, Strctural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin